Improving the detection efficiency and modulation transfer function of lens-coupled indirect X-ray imaging detectors based on point spread functions simulated according to lens performance parameters - Wang, Yanping (Journal of synchrotron radiation, 2018)
Lens-coupled indirect X-ray imaging detectors have the advantage of high resolution and the disadvantage of low detection efficiency. Using thicker single-crystalline films (SCFs) can improve the detection efficiency. However, the image quality will become worse due to the degradation of the point spread function (PSF) and modulation transfer function (MTF). This disadvantage can be improved by deconvolution with the PSF, which is unknown. In this article, a method was established to acquire the PSF based on a simulation of the imaging process for a lens-coupled indirect X-ray imaging detector. Because the structural parameters of commercial lenses cannot usually be obtained, the PSFs were calculated from lens performance parameters. PSFs were calculated using the conditions of 12 keV X-ray energy, 10× and 40× magnification objectives and 4.6 µm- and 20 µm-thick GGG:Tb scintillators. These were then used to deconvolve images of an Xradia resolution test pattern taken under the same conditions. The results show that after deconvolution the MTF had been clearly improved for both the 4.6 µm- and 20 µm-thick SCFs, indicating that the image has better quality than before deconvolution. Furthermore, a PSF deconvolution was performed on mouse brain tissue projection images, and the original and deconvolution projection images were used to perform computed-tomography reconstruction; the result proved that the method was effective for improving the image quality of low-contrast samples. Therefore, this method shows promise in allowing the use of thick SCFs to improve the detection efficiency while maintaining good image quality